WORKSHOP DAN SOSIALISASI PENGGUNAAN ALAT PRAKTIKUM IPA SEKOLAH DASAR DI SDN PULO PANJANG - Diana Ayu Rostikawati; Dedy Khaerudin; Elga Sandi Kiawati (National Conference on Applied Business, Education, & Technology (NCABET), 2021)
Science learning in elementary schools should more emphasis on process through practicum activities, currently science learning in the class is still limited to delivering theory and rarely invites students to do practicals because of the limitations of practicum tools owned by the school. Based on observations, this is also experienced by science teachers at SDN Pulo Panjang. Based on these problems, community service activities were carried out in the form of workshops and socialization of use science practicum tools, this activity consisted of two steps, e.g. preparation and implementation. At  preparation step, simple practicum tools are produced for science practicum, then these practicum tools are demonstrated at implementation step. At implementation step, the speaker explained and demonstrated several practicums related to electricity & magnetism and pressure materials. There are several things that participants gained after holding this workshop, e.g. 1) Knowledge, after the workshop it was seen that participants got new knowledge about implementation of elementary science practicum, 2) Skill, participants seemed to have tskills to carry out elementary science practicum activities, and 3) Products, after the workshop, science practicum tools will be given to the school, science practicum tools provided are equipped with guides/modules